Lower Urinary Tract Dysfunction in Uncommon Neurological Diseases – Part IV: Infections, Inflammatory, Toxic, and Structural Disorders – A NUPC Report - Charalampos Konstantinidis; Ryuji Sakakibara; Desiree Vrijens; Glenn T. Werneburg; Blayne Welk; Stephanie Kotes; Marcus J. Drake; Christina – Anastasia Rapidi; Cristiano M. Gomes; Luis Abranches-Monteiro; Kadir Onem; Stefan de Wachter; et al. (Continence)
The manuscript examines the impact of various rare neurological disorders on lower urinary tract dysfunction (LUTD), building upon previous parts of this series. It discusses several infections and their sequelae, such as Neuroborreliosis (Lyme Disease), Herpes Zoster (HZ), and Neurosyphilis. Lyme Disease is a vector-borne infection leading to storage and voiding symptoms. Herpes Zoster (HZ) is associated with various types of LUTD due to its effect on spinal nerves. Neurosyphilis, historically, is a common cause of LUTD due to the degeneration of the spinal cord. In the manuscript, other miscellaneous conditions, such as Radiation Myelopathy, Decompression Sickness and Charcot Spine, are also discussed. Radiation Myelopathy is a chronic condition affecting bladder function post-radiation therapy. Decompression Sickness occurs in scuba divers and can lead to LUTD as a neurological complication. Charcot Spine represents a destructive spinal condition that can lead to LUTD and may require intensive management. Some degenerative disorders such as Progressive Multifocal Leucoencephalopathy (PML), Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL), RSF1 related disorder – CANVAS (Cerebellar Ataxia, Neuropathy, Vestibular Areflexia Syndrome), Acute Disseminated Encephalomyelitis (ADEM) and Spinal Cord Sarcoidosis which have varying impacts on LUT function are also included in this report. Additionally, the paper includes two metabolic and toxic myelopathies (severe B12 deficiency and Nitrous oxide myelopathy), which may cause LUTD.The document emphasizes the necessity for urologists to recognize and manage LUTD in patients with these uncommon neurological conditions, promoting a comprehensive understanding of their overlaps in clinical symptoms. The overall goal is to better inform clinicians and aid in patient management by summarizing current knowledge and encouraging further research. This serves as the fourth installment in a series aiming to provide insights into rare neuro-urological diseases.